Does Paternity Leave Reduce Fertility? - Lídia Farré; Libertad Gonzalez (Institute of Labor Economics (IZA), 2018)
We find that the introduction of two weeks of paid paternity leave in Spain in 2007 led to delays in subsequent fertility. Following a regression discontinuity design and using rich administrative data, we show that parents who were (just) entitled to the new paternity leave took longer to have another child compared to (just) ineligible parents. We also show that older eligible couples were less likely to have an additional child within the following six years after the introduction of the reform. We provide evidence in support of two potentially complementary channels behind the negative effects on subsequent fertility. First, fathers' increasing involvement in childcare led to higher labor force attachment among mothers. This may have raised the opportunity cost of an additional child. We also find that men reported lower desired fertility after the reform, possibly due to their increased awareness of the costs of childrearing, or to a shift in preferences from child quantity to quality.
Keywords: J48; J13; J16; 330; paternity leave; fertility; labor market; gender; natural experiment